A Study of the Relationship between Transformational Leadership Style and Situational Factors for Successful Operation at Assumption Samutprakan School, Thailand - Gorjian, Maliheh (Scholar: Human Sciences, 2014)
This correlational study examined the relationship between transformational leadership style and three situational factors (leader-member exchange or LMR, task structure or TS, and position power or PP) for successful operation at Assumption Samutprakarn School, Thailand. To meet the study’s objectives, all 99 administrators and academic departments of the target school were given a survey questionnaire to complete (Multi-Factor Leadership Questionnaire–to measure transformational leadership style, Situational Factor Questionnaire–to measure the three situational factors, and researcher-constructed questions aimed at depicting the demographic profile of the participants). The major findings of this study were: (1) The school administrators and academic departments perceived that they have high transformational leadership style, high leader-member relations, high task-structure, and high position power; (2) Transformation leadership style was not found to be significantly related to the leader-member relations situational factor (p>.05); (3) Transformational leadership style is positively and significantly related to the task-structure situational factor (p<.01); and (4) Transformational leadership style was positively and significantly related to the position power situational factor (p<.001).